The witching wind - Lloyd, Natalie (New York : Scholastic Press, 2024)
Eleven-year-olds Roxie and Grayson share a problem, the adults they depend on have vanished, taken by the Witching Wind that "steals" what people love most, and together they must find a way to overcome it.
new kids book 2024 fall.
Ages 8-12
Grades 4-6.
Keywords: Magic -- Juvenile fiction; Missing persons -- Juvenile fiction; Winds -- Juvenile fiction; Grandmothers -- Juvenile fiction; Sisters -- Juvenile fiction; Friendship -- Juvenile fiction; Winds -- Fiction; Sisters -- Fiction; JUVENILE FICTION / Fantasy & Magic; JUVENILE FICTION / Social Themes / Bullying; Magic -- Fiction; Missing persons -- Fiction; Grandmothers -- Fiction; Friendship -- Fiction